At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To simplify the expression [tex]\(\log_a(\sqrt{2}) + \log_a(8) + \log_a\left(\frac{1}{2}\right)\)[/tex] and express it in the form [tex]\(p \log_a(2)\)[/tex], we can use logarithm properties. Let's break it down step-by-step:
1. Simplify [tex]\(\log_a(\sqrt{2})\)[/tex]:
- Recall that [tex]\(\sqrt{2} = 2^{1/2}\)[/tex].
- By the power rule of logarithms, [tex]\(\log_a(2^{1/2}) = \frac{1}{2} \log_a(2)\)[/tex].
- So, [tex]\(\log_a(\sqrt{2}) = \frac{1}{2} \log_a(2)\)[/tex].
2. Simplify [tex]\(\log_a(8)\)[/tex]:
- Recall that [tex]\(8 = 2^3\)[/tex].
- By the power rule of logarithms, [tex]\(\log_a(2^3) = 3 \log_a(2)\)[/tex].
- So, [tex]\(\log_a(8) = 3 \log_a(2)\)[/tex].
3. Simplify [tex]\(\log_a\left(\frac{1}{2}\right)\)[/tex]:
- Recall that [tex]\(\frac{1}{2} = 2^{-1}\)[/tex].
- By the power rule of logarithms, [tex]\(\log_a(2^{-1}) = -\log_a(2)\)[/tex].
- So, [tex]\(\log_a\left(\frac{1}{2}\right) = -\log_a(2)\)[/tex].
Now we combine all the simplified expressions:
[tex]\[ \begin{align*} \log_a(\sqrt{2}) + \log_a(8) + \log_a\left(\frac{1}{2}\right) &= \frac{1}{2} \log_a(2) + 3 \log_a(2) - \log_a(2)\\ &= \left(\frac{1}{2} + 3 - 1\right) \log_a(2)\\ &= \left(\frac{1}{2} + 2\right) \log_a(2)\\ &= \left(\frac{1}{2} + \frac{4}{2}\right) \log_a(2)\\ &= \left(\frac{5}{2}\right) \log_a(2). \end{align*} \][/tex]
Thus, the expression simplifies to:
[tex]\[ \frac{5}{2} \log_a(2). \][/tex]
Therefore, in the form [tex]\(p \log_a(2)\)[/tex], we have [tex]\(p = \frac{5}{2}\)[/tex].
1. Simplify [tex]\(\log_a(\sqrt{2})\)[/tex]:
- Recall that [tex]\(\sqrt{2} = 2^{1/2}\)[/tex].
- By the power rule of logarithms, [tex]\(\log_a(2^{1/2}) = \frac{1}{2} \log_a(2)\)[/tex].
- So, [tex]\(\log_a(\sqrt{2}) = \frac{1}{2} \log_a(2)\)[/tex].
2. Simplify [tex]\(\log_a(8)\)[/tex]:
- Recall that [tex]\(8 = 2^3\)[/tex].
- By the power rule of logarithms, [tex]\(\log_a(2^3) = 3 \log_a(2)\)[/tex].
- So, [tex]\(\log_a(8) = 3 \log_a(2)\)[/tex].
3. Simplify [tex]\(\log_a\left(\frac{1}{2}\right)\)[/tex]:
- Recall that [tex]\(\frac{1}{2} = 2^{-1}\)[/tex].
- By the power rule of logarithms, [tex]\(\log_a(2^{-1}) = -\log_a(2)\)[/tex].
- So, [tex]\(\log_a\left(\frac{1}{2}\right) = -\log_a(2)\)[/tex].
Now we combine all the simplified expressions:
[tex]\[ \begin{align*} \log_a(\sqrt{2}) + \log_a(8) + \log_a\left(\frac{1}{2}\right) &= \frac{1}{2} \log_a(2) + 3 \log_a(2) - \log_a(2)\\ &= \left(\frac{1}{2} + 3 - 1\right) \log_a(2)\\ &= \left(\frac{1}{2} + 2\right) \log_a(2)\\ &= \left(\frac{1}{2} + \frac{4}{2}\right) \log_a(2)\\ &= \left(\frac{5}{2}\right) \log_a(2). \end{align*} \][/tex]
Thus, the expression simplifies to:
[tex]\[ \frac{5}{2} \log_a(2). \][/tex]
Therefore, in the form [tex]\(p \log_a(2)\)[/tex], we have [tex]\(p = \frac{5}{2}\)[/tex].
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.